School Production Unit: A Production-based Learning Model in the Context of TVET Polytechnic Institutions - Thapa, Harish Singh (Journal of Technical and Vocational Education and Training, 2021)
School-based production unit is a part a school practice area where material and human inputs could be combined for the creation of goods or provision of services. It is one of the important categories of work-based learning among cooperative work, field trips, internship and youth apprenticeship. Production-based learning model is a set of procedures that need to be adopted by the instructor to facilitate students to learn actively, interactively and in a participatory way, so as to produce either goods or services needed by society. This model can facilitate students in preparing to enter the world of work and gain competence as well as the entrepreneurial spirit. School-based production unit promotes work-based learning, increases the relevance of the curriculum, promote academic achievement and employability skill. It enhances entrepreneur sprit of learners, helps in income boost, increases the cooperation/collaboration ability with society and market likewise improves learning motivation, creativity and attitudes. Management of seed capital, human resources, modalities of operation and benefit sharing among stakeholders from income of products or services are major issues of production units. These issues should address before the planning of production.